The Effect of Nurse Work Ability and Motivation on the Quality of Health Services in Centro Saúde Same SubDistrito, Manufahi Distrito, 2011 - Cleofas da Costa Seixas; Levi Anatolia S.M. Exposto (Indonesian Journal of Multidisciplinary Science, 2021)
The development of health services will include good values, including increasing the quality and quantity of nurses and preparing facilities and infrastructure as well as the use of modern tools as a tool for health services to the community, which is the embodiment of nurses as state assets and community assets in carrying out their duties. Centro Saúde Sub-Distrito Same as a partner agency of government institutions that deal directly with the community in providing health services in the form of Centro Sade should provide excellent service quickly, carefully, and accurately without forgetting the human and legal aspects. The aim of this research is to determine the effect of the ability and work motivation of nurses on the quality of health services at the Centro Saúde Sub-distrito Same, Distrito Manufahi in 2011. The method used in this study was a descriptive analytic survey method (Population). The magnitude of the correlation effect of the X1 ability variable on the Y health service quality variable is 0.7272 x 100% = 53% while the remaining 47% is determined by other factors. (2) the magnitude of the correlation effect of the X2 Motivation variable on the Y health service quality variable is 0.4832 x 100% = 0.23% while the remaining 77% is determined by other factors. And (3) the magnitude of the relationship between the variables of ability (X1) and work motivation (X2) on the quality of health services Y is 0.3882 x 100% = 15.1% while the remaining 84.9% is influenced by other factors. The study found that the effect of the ability variable (X1) and nurses' work motivation (X2) on the quality of health services (Y) of 0.76 was strong. While the joint contribution (simultaneous) of the variables X1 and X2 to Y or the determinant coefficient = r2 x 100% or 0.762 x 100% = 58% while the remaining 42% is influenced by other factors.